2012
DOI: 10.1007/s12192-012-0341-7
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock proteins and survival strategies in congeneric land snails (Sphincterochila) from different habitats

Abstract: Polmunate land snails are subject to stress conditions in their terrestrial habitat, and depend on a range of behavioural, physiological and biochemical adaptations for coping with problems of maintaining water, ionic and thermal balance. The involvement of the heat shock protein (HSP) machinery in land snails was demonstrated following short-term experimental aestivation and heat stress, suggesting that land snails use HSPs as part of their survival strategy. As climatic variation was found to be associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Mizrahi et al () even found that evolution selects snails for reduced Hsp70 expression in harsh environments. Also, Mizrahi, Heller, Goldenberg, and Arad () found reduced expression of Hsps in the desert‐living Sphincterochila zonata and interpreted this as being indicative of a strategy that avoids the fitness consequences of continuous Hsp upregulation. Similar results have been published for other stress‐tolerant populations of numerous taxa in addition to snails (Arts et al, ; Bettencourt, Feder, & Cavicchi, ; Haap & Köhler, ; Köhler, Eckwert, Triebskorn, & Bengtsson, ; Köhler, Zanger, Eckwert, & Einfeldt, ; Krebs & Feder, ; Lansing, Justesen, & Loeschcke, ; Sørensen, Dahlgaard, & Loeschcke, ; Sørensen, Michalak, Justesen, & Loeschcke, ; Zatsepina et al, ).…”
Section: Molecular Adaptationsmentioning
confidence: 99%
“…Mizrahi et al () even found that evolution selects snails for reduced Hsp70 expression in harsh environments. Also, Mizrahi, Heller, Goldenberg, and Arad () found reduced expression of Hsps in the desert‐living Sphincterochila zonata and interpreted this as being indicative of a strategy that avoids the fitness consequences of continuous Hsp upregulation. Similar results have been published for other stress‐tolerant populations of numerous taxa in addition to snails (Arts et al, ; Bettencourt, Feder, & Cavicchi, ; Haap & Köhler, ; Köhler, Eckwert, Triebskorn, & Bengtsson, ; Köhler, Zanger, Eckwert, & Einfeldt, ; Krebs & Feder, ; Lansing, Justesen, & Loeschcke, ; Sørensen, Dahlgaard, & Loeschcke, ; Sørensen, Michalak, Justesen, & Loeschcke, ; Zatsepina et al, ).…”
Section: Molecular Adaptationsmentioning
confidence: 99%
“…Furthermore, in X. derbentina, seasonal and intraspecific variations in Hsp70 induction could be found, leading to different survival strategies in X. derbentina populations (Dieterich et al, 2013;Troschinski et al, 2014). Generally, it is known that Hsp induction is used as an important survival strategy in land snails living under extreme environmental conditions Mizrahi et al, 2012). In this context, Hsps are essential for 'repairing' partly malfolded proteins due to damaging effects of ROS, so an upregulation of these proteins may be important for an organism's cellular fitness (de Oliveira et al, 2005).…”
Section: Research Articlementioning
confidence: 99%
“…A decrease in HSP expression in aestivating frogs goes hand-in-hand with the suppressed protein synthesis in the muscles and may reflect lower protein turnover rates during aestivation [41,52]. Similarly, other aestivating species such as land snails also decrease HSP expression during quiescence [53, 54] and sharply increase it during arousal [55].…”
Section: Discussionmentioning
confidence: 99%